Revisión narrativa del quiste dentígero y ameloblastoma unilocular como patologías asociadas a los capuchones pericoronarios. (2020)
Introduction: the tooth formation is given by an embryological process called odontogenesis. This process is carried out in two phases: morphogenesis and histogenesis. Both phases occur continuously and the formation of the coronary development occurs equally in stages: bud or bud stage, cap stage, bell stage and follicular stage, with their theories, chronology and determined eruption sequence. If there is a delay greater than six months, it should be investigated whether there is agenesis or if the tooth is included, which is the reason for our interest. The mandibular third molars present a greater frequency of inclusion, followed by the maxillary third molars and the maxillary canines. The early detection of radiological changes (pericoronary caps greater than 2.5mm) that occur in the pericoronary cap of the included teeth and the histopathological differentiation of these caps is something that is not done frequently. These included tooth pericoronary caps have pluripotential stem cells with the ability to differentiate and whose differentiation could progress to tumor lesions (formation of dentigerous cysts, odontogenic keratocyst, and ameloblastoma, among others). Objective. To evaluate scientific literature about dentigerous cyst and ameloblastoma as the most frequent pericoronary pathologies in dental practice. Methods:A narrative literature review was performed, for this purpose the following bibliographic databases were chosen as documentary sources: Pubmed, Scopus and Bireme. Likewise, medical journals and articles from specialized journals accessible and known by the authors of the present study were evaluated. Results. Considering that the main objective of this study is to evaluate scientific literature about dentigerous cyst and ameloblastoma as the most frequent pericoronary pathologies in dental practice, 16 studies were analyzed in which it was confirmed that dentigerous cyst and ameloblastoma are in this order the most frequent pathologies detected with respect to the groups in which they are classified by the OMS as tumors and cysts. The age range in which the dentigerous cyst is most present is between 20 and 30 years old, it predominates in the female sex with 57% and almost unanimously in this table is evident that the anatomical region where the cyst is most frequently observed is in the posterior mandibular area in 86% of cases, radiographically the cyst is seen as radiolucent areas greater than 2 mm associated with included third molars, and histologically they referenced stratified squamous epithelium in 11.5%, most of The studies analyzed did not include a histological report. Respect to ameloblastoma, we can conclude that it occurs more frequently between 15 to 30 years of age, almost unanimously, all the articles agree that the male gender is the gender in which this pathology, appear the most, associated with the mandibular body in higher percentage and only 37 cases are referenced to included teeth, however 73% of the cases studied report the presence of a uniquistic image at the radiographic level, and the anatomical area where this pathology is greatest is the body and mandibular branch 67% Histologically 60% is associated with the plexiform type, which according to the classification would be the uniquistic Type III. Conclusion. It is of great importance to carry out a good histopathological analysis of the tissues originating from the dentigerous cyst, since cellular changes can occur in some areas of the cystic wall, which must be considered for their respective evaluation and analysis. The complete surgical removal of the dentigerous cyst aims to eliminate its recurrence and the possible formation of pathologies with more aggressive behavior. The Ameloblastoma being a slow growing lesion that is usually diagnosed by chance findings at the radiographic level, it is vitally important to provide all the information to the patient regarding its management, due to its aggressive behavior, it can cause large dental losses.